Artificial intelligence and robotics in education: advantages and challenges - Chernenko Nataliia; Korablov Viktor (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
The article discusses the relevance of using artificial intelligence (AI) and robotics technologies in modern Ukrainian education. The aim of the research is to substantiate the role of artificial intelligence (AI) and robotics in education by summarizing and systematizing the advantages and challenges of their use in educational institutions. The research utilized scientific articles, studies, and reports from international peer-reviewed journals. The research methods included literature analysis, review of modern technologies, and comparative analysis of the practices of using AI and robotics worldwide and in Ukraine. Two approaches to the use of modern technologies in the educational process are considered. Firstly, the focus is on the use of AI technologies to enhance the quality of working conditions for educators and free up their time, allowing them to devote more attention to the creative aspects of teaching. Secondly, the use of robotics in education as a tool for the programming process aims to increase student engagement and stimulate their project activities. These approaches will help educators not only enhance their professional competencies but also provide learners with a unique and practical experience in acquiring competencies that meet the current standards of the New Ukrainian School (NUS). The advantages of using AI and robotics in education have been identified: personalization of learning (AI allows for the adaptation of the educational process to the individual needs of each student, enhancing the effectiveness of material assimilation); automation of routine tasks (the use of AI for automating administrative tasks frees up educators' time, enabling them to focus on creative and pedagogical activities); motivation and engagement of learners (robotics stimulates students' interest in learning through project activities and practical tasks, increasing their engagement and motivation); development of technical skills (the use of robots in the educational process contributes to the development of technical skills, critical thinking, and creative abilities of students). Certain challenges have been identified: ethical and social issues (the use of AI raises questions of privacy, bias, and impact on employment, which require careful regulation); funding for the implementation process (although the cost of technologies is decreasing, the initial expenses for implementing AI and robotics can be significant for some educational institutions); the necessity of training educators for implementation (adequate training and professional development for educators must be ensured).